PEMAKAIAN ARAHAN AMALAN DI MAHKAMAH SYARIAH MENURUT PERSPEKTIF HUKUM SYARAK: SATU ANALISIS - Zubaidi Sulaiman; Ahmad Hidayat Buang (Ulumuna: Jurnal Studi Keilsman, 2021)
Practice Direction has been introduced in the Syariah Court in Malaysia since 2000. The application of Practice Direction is an effort towards creating every Syariah Courts in Malaysia to have the same practice and standard of operation and proceedings. A qualitative approach using library research aims to analyze and clarify the basics of the Practice Direction application based on the Islamic Law perspective. Surveys to Islamic legal texts found that there was no specific discussion related to the Court Practice Direction in its form today. However, the findings of the study show that the application of Practice Direction in the Syariah Court is premised on Syariah Law through the nas-nas al-Quran and Al-Hadith, and the practice of companion. It also complies with Islamic principles such as method of the istislah, istihsan, taysir, raf’u al-haraj, avoiding masyaqqah and dharar as well as saddu zara'i in the framework of the implementation of Siasah Syar’iyyah. In addition, the application of Practice Directions corresponds with the Maqasid Syariah Ammah and the maqasid of the judiciary itself which is to uphold justice. The results of this study are very significant to further strengthen the findings of the previous research on the validity of Practice Direction as one of the main references in the Syariah Court other than the statute law in force.